EVALUASI ANGGARAN BELANJA PEGAWAI TUNJANGAN KINERJA SEBELUM DAN MASA PENDEMIK COVID-19 PADA KANTOR UNIT PENYELENGGARA BANDAR UDARA KELAS II KASIGUNCU POSO TAHUN 2019 – 2021 - Suaib Suaib; Ira Geraldina; Muhammad Din (ITB AAS Indonesia Surakarta, 2024)
This research aims to find out the implementation of the provision of civil servant performance allowances at the Office of the Class II Airport Organizing Unit Kasiguncu Poso before and during Covid-19 the 2019 - 2021 presidential period. The approach used is a qualitative approach using data collection techniques carried out through interviews and documentation. In accordance with the research conducted, writing that is qualitative descriptive then the technical analysis of data used is to answer and solve problems by doing a thorough and complete understanding and deepening of the objects studied to obtain descriptive conclusions in accordance with the conditions and time of the research. The results showed that, how to evaluate the employee spending budget for performance benefits before and during the Covid-19 pandemic at the Kasiguncu Poso Class II Airport Organizing Unit Office in 2019 – 2021. The evaluation carried out by the leadership in evaluating the employee expenditure budget in the environment of the Kasiguncu Poso Class II Airport Organizing Unit Office has gone well based on fiscal policy theory. What are the driving factors and obstacles to the evaluation of employee spending budgets for performance benefits before and during the Covid-19 pandemic at the Kasiguncu Poso Class II Airport Organizing Unit Office in 2019 – 2021. One of the driving and inhibiting factors is communication.